2007
DOI: 10.1111/j.1469-8749.2007.02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Shaken baby syndrome: the quest for evidence

Abstract: Shaken baby syndrome (SBS), characterized by the triad of subdural haemorrhage, retinal haemorrhage, and encephalopathy, was initially based on the hypothesis that shaking causes tearing of bridging veins and bilateral subdural bleeding. It remains controversial. New evidence since SBS was first defined three decades ago needs to be reviewed. Neuropathology shows that most cases do not have traumatic axonal injury, but hypoxic–ischaemic injury and brain swelling. This may allow a lucid interval, which traumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…2 This reported mechanism of injury has been questioned and has undergone scientific review and experimentation using models/ dummies, animals, and cadavers. 7,12,22,23 Based on the results of these studies, it has been difficult to prove that shaking is sufficient to produce SDH. 22 As a result of this, together with the fact that the terminology describing this type of injury continues to evolve, we have concluded that it is important to avoid terminology that assumes mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…2 This reported mechanism of injury has been questioned and has undergone scientific review and experimentation using models/ dummies, animals, and cadavers. 7,12,22,23 Based on the results of these studies, it has been difficult to prove that shaking is sufficient to produce SDH. 22 As a result of this, together with the fact that the terminology describing this type of injury continues to evolve, we have concluded that it is important to avoid terminology that assumes mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…SBS can be considered as a common part in the broader spectrum labeled "non-accidental head injury" (NAHI), encompassing further, albeit rarer, forms of inflicted infantile neurotrauma (shaken-impact syndrome, pure blunt head trauma, crush injury, etc.). For the pathologist asked to give written or oral expertise in court, more than a basic knowledge and understanding of the entire spectrum is absolutely mandatory-even if the scientific basis of this condition is only poorly understood [111]. The present review aims at summarizing the present knowledge and most recent scientific data of ocular pathology in SBS and other forms of NAHI for the specific scope of the forensic practitioner.…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%
“…The finding of the triad of subdural hematoma, retinal hemorrhage, and encephalopathy had gained acceptance as being "evidence" indicative of intentional infant injury; commonly referred to as the "shaken baby syndrome" [21]. However, the reliability and validity of using the clinical and pathological triad associated with the shaken baby syndrome to definitively indicate intentional injury has been challenged [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%